Low Quality of Warfarin Therapy is Associated With Female Gender but Not With Polypharmacy in Patients With Atrial Fibrillation - Takamoto, Kojiro; Sakamoto, Jun-ichi; Ito, Satoyasu; Kimura, Takeshi; Manabe, Eri; Shikata, Toshiyuki; Asakura, Masanori; Ishihara, Masaharu; Tsujino, Takeshi (Frontiers in Pharmacology, 2021)
Background: We examined the impact of polypharmacy on the quality of the anticoagulation therapy in patients with atrial fibrillation. We also examined the factors that affect the stability of warfarin therapy. Methods and Results: This retrospective study was conducted using data from 157 consecutive outpatients with atrial fibrillation in a single tertiary referral hospital. Patients who were prescribed warfarin continuously and for whom PT-INR was examined at least three times in a year were included in this study. We examined the quality of warfarin therapy using time in the therapeutic INR range (TTR), percentage of PT-INR determinations in range (PINRR), and the coefficient variation (CV) of PT-INR. We found that the number of prescribed medicines was significantly associated with high BMI and low eGFR, but not with TTR, PINRR, and the coefficient variation of PT-INR in patients with atrial fibrillation. We also found that female gender was independently associated with low PINRR in this study population. Conclusion: Polypharmacy did not deteriorate the quality of warfarin therapy in patients with atrial fibrillation treated in the tertiary referral hospital. Female gender was an independent predictor of the low quality of warfarin therapy.